Using serious leisure theory to explore the experiences of people walking the Camino - Yih, Hsin-Yu (The University of Edinburgh, 2025)
This study aims to investigate the differences in flow experiences between individuals walking alone and those walking with companions along the Camino de Santiago in Spain. The researcher conducted fieldwork in Arzúa, Spain, collecting both questionnaires and implementing interviews directly along the pilgrimage route. A mixed-methods approach was used, dividing participants into two groups: those walking alone and those walking with companions. Quantitative data were collected using the Flow State Questionnaire, with ANOVA and U-tests employed to determine if there were significant differences in flow experiences between the two groups. Semi structured interviews served as the primary source for qualitative data, which were subsequently coded and categorized to reduce single-method bias and to enhance cross validation. Results showed that solo walkers experienced higher flow across all nine dimensions compared to those walking with companions. However, statistically significant differences emerged specifically in the dimensions of “transformation of time,” “action-awareness merging,” “autotelic experience,” and “feedback.” Qualitative data further highlighted that walking alone allowed individuals to concentrate more fully on the act of walking, enriching their overall experience. The study also found that religious factors influence flow on the Camino, with Catholics having higher flow experiences levels compared to non-Catholics or those without religious affiliations. Additionally, from the perspective of serious leisure theory, long distance hiking on the Camino can indeed be categorized as a form of serious leisure, enhancing both the sense of achievement and the personal growth of participants.
Keywords: flow experience; serious leisure